2015
DOI: 10.1007/s11056-015-9491-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and forest restoration: a review and meta-analysis of tree growth responses

Abstract: Biochar'', or charcoal intended for use as a soil amendment, has received great attention in recent years as a means of enhancing carbon sequestration and soil properties in agricultural systems. Here we address the potential for biochar use in the context of forest restoration, reviewing relevant experimental studies on biochar use in forest ecosystems, the properties of chars generated from wood waste material, and available data on tree growth responses to biochar. To our knowledge the earliest mention of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 79 publications
6
148
9
Order By: Relevance
“…BCA applications and NS, in general, significantly increased stem diameter, seedling height, RDM, TFM, SDM, and QID of seedlings, in comparison with BC and CS substrates (Figure 3). These results agree with the literature, which, in general, shows strong positive growth responses of seedlings to the use of biochar in the nursery phase (Cernansky, 2015;DeLuca et al, 2015;Ghosh et al, 2015;Thomas & Gale, 2015).…”
Section: Resultssupporting
confidence: 92%
“…BCA applications and NS, in general, significantly increased stem diameter, seedling height, RDM, TFM, SDM, and QID of seedlings, in comparison with BC and CS substrates (Figure 3). These results agree with the literature, which, in general, shows strong positive growth responses of seedlings to the use of biochar in the nursery phase (Cernansky, 2015;DeLuca et al, 2015;Ghosh et al, 2015;Thomas & Gale, 2015).…”
Section: Resultssupporting
confidence: 92%
“…Amiata (hereafter: "beech" forests). Mean annual rainfall and temperature in this area vary from 780.7 mm and 15.4 °C along the coast to 1.641 mm and 8.7 °C on the Apennines (period 1961-1990-Regione Toscana 2016 …”
Section: Study Areamentioning
confidence: 94%
“…The use of vegetative compost increases microbial activity and protects against erosion (Ruttens et al 2006;Carlson et al 2015) while biochar immobilizes toxic heavy metals owing to its high pH, large surface area for sorption of metals, alkalinity, and ash content (Namgay et al 2010;Paz-Ferreiro et al 2014). A meta-analysis of recent studies on biochar responses of woody plants concluded that addition of biochar has potential for large tree growth responses, with 41% average increase in biomass, and hence holds promise for forest restoration (Thomas and Gale 2015).…”
Section: Biological Methodsmentioning
confidence: 99%